2011
DOI: 10.1186/1752-1947-5-360
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent, sequential, bilateral deep cerebellar hemorrhages: a case report

Abstract: IntroductionHypertensive intra-cerebral hemorrhage is usually a one-time event and recurrences are rare. Most recurrences develop as part of long-term failure of blood pressure control. The site of the re-bleed is usually limited to the basal ganglia and thalami.Case presentationWe report the case of a 59-year-old hypertensive Caucasian woman who developed two sequential, right- and then left-sided, deep cerebellar hemorrhages. The second hemorrhage followed the first one by 57 days, at a time when her blood p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…[23] As for the hemorrhagic stroke, it has been suggested that the presence of LVH is a mere marker of chronic hypertension and wide-spread end-organ damage, including intracerebral Charcot-Bouchard microaneurysm formation and rupture. [16,24,25] According to Di Tullio and colleagues, [26] LVH appeared to be independently associated with stroke, regardless of the age, sex, and ethnicity of the target population, and this is consistent with our observations. However, the increased prevalence among our Kurdish hemorrhagic stroke patients needs further analysis.…”
Section: Discussionsupporting
confidence: 92%
“…[23] As for the hemorrhagic stroke, it has been suggested that the presence of LVH is a mere marker of chronic hypertension and wide-spread end-organ damage, including intracerebral Charcot-Bouchard microaneurysm formation and rupture. [16,24,25] According to Di Tullio and colleagues, [26] LVH appeared to be independently associated with stroke, regardless of the age, sex, and ethnicity of the target population, and this is consistent with our observations. However, the increased prevalence among our Kurdish hemorrhagic stroke patients needs further analysis.…”
Section: Discussionsupporting
confidence: 92%
“…Poorly controlled blood pressure may lead to sequential haemorrhage in the cerebellum leading to bilateral haematoma due to rupture of Charcot–Bouchard micro-aneursyms 9. In the cerebellum, small penetrating branches arising from superior cerebellar arteries are the usual site of such micro-aneurysms which occur because of the degenerative effect of long-standing hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…We reported on this patient previously2 and we found that her blood pressure was well controlled after developing her very first primary ICH. Her examination notes stated that the patient's blood pressure was again well controlled with antihypertensive medications after developing the second cerebellar haemorrhage.…”
Section: Discussionmentioning
confidence: 70%